East Asia's Dynamic Development Model and the Republic of Korea's Experiences - McNulty, Mary (The World Bank, 2003)
No region has been more dynamic in recent years than East Asia. Despite its successful economic development, evaluations of the East Asian development model have often been capricious, shifting from "miracle" to "cronyism." How can we explain East Asia's ups and downs consistently? To respond to this challenge, it is necessary to study the progress of East Asian development and to trace the influence of Asian cultural values. This study mainly focuses on cultural aspects of economic progress and analyzes East Asia's philosophical and historical backgrounds to explain the dynamic process. East Asians believe that balance between opposite but complementary forces, Yin and Yang, will ensure social stability and progress. Through repeated rebalancing to maintain harmony, the society comes to maturity. In traditional East Asian societies, a balance was maintained between Confucianism (Yang) and Taoism, Buddhism, and other philosophies (Yin). In modern societies, the challenge is to balance traditional systems (Yang) and Western style capitalism (Yin). This East Asian development model explains the Republic of Korea's rise, fall, and recovery. Korea was a poor country until the early 1960s, during the time when spiritualism (Yang) dominated. From the 1960s through the 1980s, Korea achieved rapid growth by finding a new balance and moving toward materialism (Yin) from spiritualism (Yang). But the failure to maintain a harmonious balance between cooperatism and collectivism (Yang) and individualism (Yin) led to major weaknesses in labor and financial markets that contributed significantly to the financial crisis in 1997. As Korea arrived at a new balance by instituting reform programs, the venture-oriented information and communication technology (ICT) industry blossomed and led to a rapid economic recovery.